Effect of perceived social support and level of hope on quality of life among chronic kidney disease patients in a tertiary care center in Chennai - A cross-sectional study - Ganeshkumar Raja NC,; Krithiga Sivakumar,; Seenivasan P, (Asian Journal of Medical Sciences, 2023)
Background: Chronic kidney disease (CKD) is a major public health problem in developing countries, adversely affecting the quality of life (QOL) of the individual and their family. Perceived social support and hope are important factors influencing the QOL. Aims and Objectives: The objectives of the study were to assess the QOL among patients with CKD and the effects of perceived social support and hope on QOL. Materials and Methods: This is hospital based cross-sectional study among CKD patients attending nephrology department, between March and November 2018. Face to face interview using Adult Hope Scale and Multidimensional Perceived Social Support scale and WHOQOL-BREF-26 was done after obtaining informed consent. Epi-info and SPSS16.0 were used for statistical analysis. t-test, ANOVA, and correlation coefficient was done to find any association. Results: Among the 152 participants, majority (70%) had fair QOL with the highest score in social relationships domain of 53 (±12), using the WHO BREF26 questionnaire. The QOL was also found to be associated with education and socio-economic status. A positive correlation between perceived social support and hope with QOL was observed. Conclusion: Majority had a fair QOL, with the highest score in social relationship domain. Positive correlation was observed between perceived social support and hope with QOL. Apart from medical treatment, the key to better health outcome depends on social support. Hence, it is imperative to highlight the importance of social support and hope at the commencement of the treatment of CKD.